Climate Change, Politics and the Press in Ireland - Robbins, David (Routledge Focus on Environment and Sustainability Ser, 2018)
Media coverage of climate change has attracted much scholarly attention because the extent of such coverage has an agenda-setting effect and because the ways in which the coverage is framed can influence public perception of and engagement with the issue. However, certain gaps in our understanding of the processes whereby such coverage is produced remain. The competition among strategic actors to influence media framing strategies is poorly understood, and the perspectives of journalists and editors are largely absent from literature. With a view to advancing our understanding of the "frame competition" around climate change and to presenting the perspectives of journalists regarding climate change as a journalistic topic, this book presents an in-depth case history of media coverage of climate change in Ireland. First, the extent of media attention for climate change is established, and the way in which such coverage is framed is also examined. Through a series of interviews, including rare and privileged access to government ministers, their media advisors, and journalists and editors, the book uncovers the contest to establish a dominant framing. The main objective of this book is to advance our understanding of the contest to establish the dominant framing of climate change in the media discourse. Although focussed on Ireland, its conclusions are of value to those seeking to better understand the dynamics of media coverage of climate change in other contexts. This book will be of great interest to students and scholars of climate change, environmental policy, media and communication studies, and Irish politics